2018
DOI: 10.3390/urbansci2030074
|View full text |Cite
|
Sign up to set email alerts
|

Urban Heat Island and Mitigation Technologies in Asian and Australian Cities—Impact and Mitigation

Abstract: n/a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…These results confirm that the roles played by the difference in energy consumption between inner city, suburban, and urban fringe areas are mainly because the cooling load of urban buildings is 13% higher than that of similar buildings in the rural-urban fringe areas. Thus, this relationship between electricity consumption and temperature has been clearly established [20,[54][55][56].…”
Section: Relationship Between Lst and Uhii With High-rise Buildings In Different Three Zonesmentioning
confidence: 93%
See 1 more Smart Citation
“…These results confirm that the roles played by the difference in energy consumption between inner city, suburban, and urban fringe areas are mainly because the cooling load of urban buildings is 13% higher than that of similar buildings in the rural-urban fringe areas. Thus, this relationship between electricity consumption and temperature has been clearly established [20,[54][55][56].…”
Section: Relationship Between Lst and Uhii With High-rise Buildings In Different Three Zonesmentioning
confidence: 93%
“…Anthropogenic parameters such as industrial heat emissions, heating, transport, or air conditioning can contribute as well to heat intensification, as the cities consume 78% of the world's energy and produce more than 60% of greenhouse gas emissions [18,19]. This increasing urbanization has a significant impact on urban microclimates and leads to warmer temperatures in cities [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…A recent modeling study based on a building located in the center of Rome, Italy, indicated that the energy consumption of cooling would be underestimated by 35%-50% if the climatic effect of the heat island is not considered (Ciancio et al, 2018). More studies related to the urban microclimate and the UHI effect and its mitigation technology solutions can be tracked down in a recent special issue of Urban Science (Yang and Santamouris, 2018).…”
Section: Question 6: How Can Local Weather Data Be Generated and Usedmentioning
confidence: 99%
“…Several researches have used the Moran's I index (Deilami et al, 2018;Mavrakou et al, 2018 andYang andSantamouris, 2018) to analyze the adverse effects of UHI and under the perspective of appropiate urban development. It is noteworthy that the main object of the technique is based on the spatial heterogeneity of the distribution of LST (for example, high or low clustering pattern and dispersed spatial distribution).…”
Section: Moran's I Indexmentioning
confidence: 99%